Працівники прокуратури як суб’єкти трудового права - Шевченко, Н. Л.; Shevchenko, N. L. (Вісник Харківського національного університету внутрішніх справ. - 2015. - № 1 (68). - С. 167-173., 2015)
Розглянуто питання правового статусу працівників прокуратури як суб’єктів трудового права. Порівняно категорії «правовий статус» та «правове становище». Досліджено вимоги до трудової правосуб’єктності працівників прокуратури. Надано пропозиції з удосконалення відповідного законодавства.

The issues of the legal status of the employees of prosecutor’s office as subjects of labor law are studied. The categories «legal status» and «legal state» are compared. The point of view that these categories are similar is grounded. Elements of the legal status of an individual are researched. It is noted that legal personality is not an element of the legal status of an individual, because it precedes the acquisition of the legal status by an individual. The elements of the legal status of an individual, according to the author’s opinion are the rights, freedoms, duties, legal guarantees of their implementation and legal liability. Special attention is paid to the fact that each of the groups of subjects of labor law has a specific legal status. Moreover, it is necessary to distinguish the subjects inside of some groups that have specific features and have a special legal state. This is fully related to such a category of subjects of labor law as employees. Thus, we can distinguish a large number of specific subjects, including the employees of prosecutor’s office within this category. These employees endowed with specific legal status under the law that allows them to participate in specific labor legal relations. The legislative requirements for labor legal personality of the employees of prosecutor’s office and legal regulation of their labor rights and duties are studied. It is concluded about the consolidation of the Articles titled «Labor rights of the employees of prosecutor’s office» and «Labor duties of the employees of prosecutor’s office» in the Law of Ukraine «On Prosecutor’s office». These Articles should provide an exhaustive list of rights and duties.

Рассмотрены вопросы правового статуса работников прокуратуры как субъектов трудового права. Сравнены категории «правовой статус» и «правовое положение». Исследованы требования к трудовой правосубъектности работников прокуратуры. Даны предложения по улучшению соответствующего законодательства.
Shevchenko, N.L. (2015), “Employees of prosecutor’s office as subjects of labor law” [“Pratsivnyky prokuratury yak subiekty trudovoho prava”], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 1, pp. 167-173.
Шевченко, Н. Л. Працівники прокуратури як суб’єкти трудового права // Вісник Харківського національного університету внутрішніх справ. - 2015. - № 1 (68). - С. 167-173.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; суб’єкти трудового права; subjects of labor law; субъекты трудового права; працівники прокуратури; трудові права; трудові обов’язки; трудова правосуб’єктність; employees of prosecutor’s office; labor rights; labor obligations; labor legal personality; работники прокуратуры; трудовые права; трудовые обязанности; трудовая правосубъектность